Designating place : archaeological perspectives on built environments in Ostia and Pompeii - Kamermans, Hans; Meer, L. Bouke van der (Archaeological studies Leiden University ;, 2020)
Spatial analysis on the basis of material culture has always been one of the mayor topics in archaeological research. 'Designating place' analyses the urban space of Roman Ostia and Pompeii in different ways: geophysical analysis, spatial analysis, iconographic analysis and epigraphic analysis. This book is based on the work of Hanna Stöger, the Leiden scholar who died in 2018. Hanna?s work in Ostia was not finished and this book contains contributions from people who inspired her, people she worked with, people she inspired and people who were presented on sessions she organized. The part on geophysics contains new data on Ostia from teams from the University of Delft in the Netherlands and from Canada and Germany. The spatial analysis discusses mainly the pro and cons of the use of Space Syntacs, the computer program Hanna used to analyse Ostia with contributions from scholars from the United Kingdom, Japan, Italy, the Netherlands and the USA. The last two parts on iconographic and epigraphic analysis consists of articles by researchers from the Netherlands and Norway.